Tradycyjne frazeologizmy biblijne o genezie psałterzowej w Psalmach Króla Dawida Bohdana Drozdowskiego - Kolmaga, Weronika (Acta Universitatis Lodziensis. Folia Linguistica, 2018)
The aim of the thesis is to show King David’s Psalms written by Bohdan Drozdowski in the light of Psalter style. Analyses are focused on traditional biblical phrases compared with a faithful translation from the Latin written by Jakub Wujek. Conducted analyses pointed to the conclusion that the amount of biblical constructions is suprisingly high. What is important they appeared not only in parallel fragments of other Psalters but also in different parts of the text. Also the author made intertextual references to other biblical books and a number of modifications. It brings the reflection that tradition is strongly present in the paraphrase but on the other hand it is creatively imitate.